CONSEQUENCES OF RURAL-URBAN MIGRATION ON THE SOURCE REGION OF UGHIEVWEN CLAN DELTA STATE NIGERIA. - Edith Ochuko AMREVURAYIRE; Vincent Nduka OJEH (European Journal of Geography)
Migration is considered as the movement of people from one geographical region to another, which may be on temporary or permanent basis. This study assessed the consequences of rural-urban migration on the source region of Ughievwen clan in Ughelli South Local Government Area. The stratified sampling technique on the basis of existing geopolitical wards was used to divide the study area into four (4) zones. Data were generated through primary and secondary sources. The primary data were generated through the administration of two hundred and sixteen (216) copies of questionnaires to respondents in the study area using the systematic sampling approach, while the secondary data were collected from journal/publications and other published materials from textbooks and official gazette. The data generated were analysed using multiple regression statistics. The findings of the study show that females migrate more than the males in Ughievwen and migration is high within the age cohorts of 15-25 years and 26-35 years. More so, migration decreases with age, and this may be due to the higher psychological cost for migration associated with older people. Most of the persons in the community had acquired just their basic education. Thus, most of them are willing to migrate to major cities to obtain higher education. It has been widely observed that the propensity to migrate increases with education. Furthermore, the study revealed that migration is affected by socioeconomic, demographic and cultural factors.